Exploring the dynamic mechanical response and mesoscopic characteristics of typical frozen rock in Yulong Copper Mine - Shoudong, Xie; Chengjie, Li; Ying, Xu; Zhongyi, Zhang; Mengqi, Wang; Qi, An (Frontiers in Materials, 2024)
Dynamic mechanical characteristic testing at low temperatures was conducted for the typical porphyry and sandstone specimens of Yulong Copper Mine in Tibet, China. The stress and strain characteristics of the specimens at different temperatures were analyzed. A dynamic constitutive model was developed by considering the initial damage. Furthermore, microscopic damage characteristics during the water-saturated rock freezing process were investigated using the PFC3D software, revealing the mechanisms of frost heave damage to rocks. The results indicated that the water-ice phase transition either enhanced or deteriorated the specimen strength at low temperatures. Specifically, freezing at −10°C and −20°C enhanced the strength of sandstone. However, freezing at −10°C enhanced the porphyry specimens, and freezing at −20°C caused significant frost swelling injury. The new constitutive equation effectively fitted the dynamic stress and strain curves for both specimens, highlighting their differences. The maximum contact force and particle contact in the frozen rock PFC3D model were affected by rock and water particle deformations. The frost swelling deformation of water particles had a more pronounced impact on specimen damage and was related to the temperature. A specific freezing temperature existed at which the increase in saturated rock strength corresponded to the maximum specimen strength at that temperature.